Chapter Lo sguardo territorialista di Leonardo da Vinci fra arte, ricerca e immagine - Poli, Daniela (Territori, 2023)
Leonardo's multifaceted experience has often been celebrated as a key historical legacy placed in a distant past. However, an interdisciplinary investigation of Leonardo's thought, studies and design intentionality, trying to combine art and science, has highlighted the cornerstones of an ante litteram territorialist vision. To the finished product, Leonardo always prefers the knowledge of the most intimate relationships among components of the territory, always understood as a living being, thus giving posterity an immense gallery of possibilities. Therefore, Leonardo's complex and integrated vision is a viaticum for the project of today's manifold territory.